The Stages Of Community Organization Based On Tuberculosis Survivors In Jember Regency - Risma Melati, Triska Ayunda; Adi Prasetyo, Franciscus; Poerwanti, Sari Dewi (KOMUNITAS, 2024)
This research investigates the stages of organizing tuberculosis survivor-based communities in Jember Regency. Drug-resistant tuberculosis (DR-TB) survivors possess empathy and a sense of urgency due to their personal experiences with the impact of DR-TB. These survivors have established a community-based organization to support DR-TB patients. The location was determined using purposive area sampling. Research informants are categorized into two groups: primary informants (chairperson, representative, and treasurer) and additional informants (DR-TB patients). Data collection techniques included non-participatory observations, semi-structured interviews, and documentation. The findings of this study indicate that the eight stages of organizing Sekawan’s TB community significantly enhance the quality and capacity of community resources, expand the community's presence, and build trust among the public and stakeholders. Moreover, the community's efforts effectively reduce stigma and discrimination against patients, improve patient welfare and recovery rates, and serve as a source of education and support for patients and their families.